Effects of Drought on the Water Use Strategies of Pure and Mixed Shrubs in the Mu Us Sandy Land - Qin Gao; Xiaohong Dang; Zhongju Meng; Yang Liu; Jiale Lou; Yu Yan; Xing Zhang (Plants)
Water resources are crucial factors that limit vegetation recovery, and rational planning of silvicultural patterns is essential for the efficient utilization of water in arid and semi-arid regions. This study examined the water utilization strategies of pure shrubs (pure stands of Artemisia ordosica and pure stands of Salix psammophila) and mixed shrubs (mixed stands of A. ordosica S. psammophila, and mixed stands of A. ordosica Caragana korshinskii) from the rainy to dry seasons using stable isotope techniques and MixSIAR modeling in the Mu Us Sandy Land in the semi-arid region of China. Mixed shrubs were significantly more effective than pure shrubs in utilizing the primary water sypply from the soil layer. During the rainy season in August, shallow soil water was used to a greater extent, contributing 33.78 ± 2.18%, with no significant difference in the contribution proportion. After a brief drought during the transition period in September, there was a significant increase in the use of the primary water-absorbing soil layer across all vegetation types, with a maximum increase of 39.53%. Conversely, during the dry season in October, after an extended drought, the contribution of the primary water supply layer to vegetation water absorption decreased compared with the transition period, with a maximum increase of only 17.88%. The results of this study revealed that variations in water conditions and vegetation configurations influence the water utilization patterns of the vegetation. This study offers a scientific basis and theoretical support for understanding ecological water use, the rationale behind vegetation establishment, and an assessment of plantation community stability in sandy regions.